BRIBERY IN THE PRIVATE SECTOR AS A CORRUPTION OFFENSE POLICY - Imentari Siin Sembiring; Pujiyono Pujiyono (Universitas Islam Negeri Alauddin Makassar, 2021)
Bribery is an act of corruption. This article aims to analyze the formulation of bribery in the private sector as a criminal act of corruption. This type of research is normative research. The results of the study concluded that bribery in the private sector is an act of corruption as regulated in UNCAC, Indonesia categorizes it as a crime but not as corruption. Problems related to the regulation of bribery in the private sector in Indonesia create ambiguity in its application so it is necessary to accommodate bribery in the private sector as a category of corruption by looking at Singapore which has also ratified UNCAC and has categorized bribery in the private sector as a criminal act of corruption.